Sudden intrauterine unexplained death: time to adopt uniform postmortem investigative guidelines? - Anna M. Lavezzi; Francesco Piscioli; Teresa Pusiol; Gianfranco Jorizzo; Stefano Ferrero (BMC, 2019)
Abstract Background Worldwide approximately 2.6 million are stillborn, mostly occurring in developing countries. In the great part these deaths are inexplicable. The evenness and standardisation of the diagnostic criteria are prerequisites to understand their pathogenesis. The core goal of this article is to propose new evidence based investigative post-mortem guidelines that should be adopted in all the Institutions especially when a fetal death, after a routine autopsy procedure, is diagnosed as "unexplained". The proposed protocol is mainly focused on the anatomopathological examination of the autonomic nervous system and in particular of the brainstem where the main centers that control vital functions are located. Methods Updated investigative guidelines for the examination of unexplained stillbirths, prevalently focused on the histological examination of the brainstem, where the main centers that are involved in monitoring the vital functions are located, are here presented. A section of this protocol concerns the Immunohistochemical evaluation of specific functional markers such as the neuronal nuclear antigen, nicotinic acetylcholine receptors, serotonin, orexin, apoptosis and gliosis. The important role of risk factors, having regard in particular to maternal smoking and air pollution is also contemplated in these guidelines. Results Specific morphological and/or functional alterations of vital brainstem structures have been found with high incidence in over 100 cases of unexplained fetal death sent to the "Lino Rossi Research Center" of the Milan University according to the Italian law. These alterations were rarely detected in a group of control cases. Conclusions We hope this protocol can be adopted in all the Institutions notably for the examination of unexplained fetal deaths, in order to make uniform investigations. This will lead to identify a plausible explanation of the pathogenetic mechanism behind the unexplained fetal deaths and to design preventive strategies to decrease the incidence of these very distressing events for both parents and clinicians. Trial registration not applicable for this study.